Pelatihan Menulis Sastra Anak Berbasis Kearifan Lokal Pada Mahasiswa PGMI IAIN Palangka Raya - Normuliati, Sri (AJAD : Jurnal Pengabdian kepada Masyarakat, 2023)
This service aims to provide knowledge and training in writing children's literature to PGMI IAIN Palangka Raya students. This community service was carried out in 5 meetings using lecture and writing workshop methods. Activities were held on May 29, 2023, May 31, 2023, June 6, 2023, June 12, 2023, and June 14, 2023, with 28 participants participating. The results obtained from this service show that using local wisdom ideas in the immediate environment is one way to develop writing skills. The result of this activity is the publication of an anthology/collection of children's literature stories by PGMI IAIN Palangka Raya students. Several types of local wisdom are raised, such as beliefs/myths that exist in Central Kalimantan society, community traditions, traditional games, traditional food, and traditional handicrafts. With this activity, it is hoped that it can improve students' writing skills, especially in writing fiction.